Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
f(3)=0, f(4)=-60
f(n) = f(n-1) + (-60)
Step-by-step explanation:
The arithmetic sequences are identified because any term n is obtained by adding or subtracting a fixed number to the previous term. That number is called the common difference.
The equation to calculate the nth term of an arithmetic sequence is:
f(n)=f(1)+(n-1)r
Where
f(n) = nth term
f(1) = first term
r = common difference
n = number of the term
The given sequence has two known terms: 120, 60, ...
The common difference is found by subtracting consecutive terms:
r = 60 - 120 = -60
Thus the next two terms are:
f(3)=120+(3-1)(-60)=120-120 = 0
f(4)=120+(4-1)(-60)=120-180 = -60
Since each term is calculated as the previous term plus -60, then the recursive formula is:
f(n) = f(n-1) + (-60)
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.